All Days 2015
DOI: 10.4043/25729-ms
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Flow Modeling for Gas Hydrates in Flow Assurance

Abstract: Multiphase flow is a central component in all flow assurance strategies in oil and gas production. The risk of plugging of flowlines due to hydrate formation is also one of the most prevailing flow assurance problems in subsea deepwater oil and gas operations. Hence, it is critical to develop a model to account for the inter-coupling of hydrates and multiphase flow. We present a new framework to model the effect of multiphase flow on hydrates and vice-versa. In the current work, we use a two-phase (gas/liquid)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…23 What has been done was to try to simulate these conditions in a laboratory loop and study the hydrate formation. [24][25][26][27][28][29][30][31][32][33][34][35][36] Turner et al 23 and Lv et al 26 proposed a hydrate formation mechanism, expressed as hydrates forming and growing as shells outside the water droplets entrained in the oil phase, as water-in-oil emulsion. Shi et al 29,30 developed an inward and outward hydrate growth shell model to describe hydrate formation in a water-in-oil emulsion system, which considered the inuences of kinetics as well as mass and heat transfer on hydrate formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…23 What has been done was to try to simulate these conditions in a laboratory loop and study the hydrate formation. [24][25][26][27][28][29][30][31][32][33][34][35][36] Turner et al 23 and Lv et al 26 proposed a hydrate formation mechanism, expressed as hydrates forming and growing as shells outside the water droplets entrained in the oil phase, as water-in-oil emulsion. Shi et al 29,30 developed an inward and outward hydrate growth shell model to describe hydrate formation in a water-in-oil emulsion system, which considered the inuences of kinetics as well as mass and heat transfer on hydrate formation.…”
Section: Introductionmentioning
confidence: 99%
“…They also confirmed that the gas–water flow pattern affected the hydrate formation rate and plugging time apparently in both systems. Joshi et al , 25 Zerpa et al , 34 Hegde et al 35 investigated the hydrate formation process in the multiphase flow system. They founded that the hydrate formation process was affected by factors such as phase interface, pressure, supercooling degree and heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, It can be concluded from the study of (Hegde, et al 2014) that the presence of hydrates causes an important change in the slugging behaviour of a system. Hence, in this case too, it is implied that a further research of the interference of hydrate formation and the slugging characteristics of the system is required in order to achieve a better understanding on the effect of hydrates in multiphase flow systems.…”
Section: Introductionmentioning
confidence: 98%
“…Multiphase flow is the major component in flow assurance studies, as it governs how the phases (gas, liquid, solid) are distributed in the flowline and is the key to capture the thermohydraulic conditions in flowlines. , The essence of multiphase flow is the distribution of the flowing phases that are characterized by the flow regime, such as stratified, stratified-wavy, and slug flow, which are common in oil and gas production systems. Such flow regimes determine how phases are dispersed under a given shear and thus when, where, and how much solid precipitates out when the conditions are appropriate.…”
Section: Introductionmentioning
confidence: 99%